2010
DOI: 10.1111/j.1463-1318.2009.01915.x
|View full text |Cite
|
Sign up to set email alerts
|

Transanal haemorrhoidal artery echodoppler ligation and anopexy (THD) is effective for II and III degree haemorrhoids: a prospective multicentric study

Abstract: Doppler-assisted ligation of the terminal branches of the haemorrhoidal arteries for II and III degree haemorrhoids is highly effective and painless. Complications are few and the technique can be performed as a day case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
2
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 28 publications
5
29
2
4
Order By: Relevance
“…It is of interest is that neither faecal urgency nor faecal incontinence was reported, confirming that use of the THD method is reliable and not detrimental to continence mechanisms [6,9,34]. Also, the resulting longterm rectal pain was limited [6,9,34]. All these features justified the significant reduction in the mean HD score as reported by patients.…”
Section: Discussionsupporting
confidence: 69%
“…It is of interest is that neither faecal urgency nor faecal incontinence was reported, confirming that use of the THD method is reliable and not detrimental to continence mechanisms [6,9,34]. Also, the resulting longterm rectal pain was limited [6,9,34]. All these features justified the significant reduction in the mean HD score as reported by patients.…”
Section: Discussionsupporting
confidence: 69%
“…This finding is inconsistent with our study, (8,16) because we observed much better outcomes (no failure), but other elements of Ramirez's study and other studies confirmed our results (4,8,10,17,18). Some studies added some modalities such as recto anal repair adjunct to DGHAL with similar results to DGHAL alone (6,16,19 (20).…”
Section: Discussioncontrasting
confidence: 57%
“…However, because the hemorrhoidal plexuses remain in place and the network of arteries and veins above them is partially blocked, secondary thrombosis may occur, as was the case in the present study and in other reports. 4,25 The 2 main weaknesses of the present study are the lack of very long-term results and the absence of a comparison among this procedure, hemorrhoidectomy, and hemorrhoidopexy regarding technical and functional results. A prospective, multicenter French study is currently in progress, with the aim of partially addressing this issue and answering the economic question of which procedure is the most cost effective.…”
Section: Discussionmentioning
confidence: 98%